Giving Consent - Schaber, Peter (Journal of moral philosophy, 2025)
By giving consent, we sometimes give permission or make it the case that we are not wronged. What does it take for an act to be an act of consent? This is the question this paper deals with. The question does not presuppose the view that consent is a communicative act. For those who take it as a mental state, the question is what does it take to express consent? It will be argued that an act is an act of consent if and only if the consent-giver believes she gives someone permission to do or omit something by performing the act. A normative intention is not required for consent. It is further argued that this view also bears on the question of what falls within the scope of consent and shows how it differs from the evidential account advocated by Tom Dougherty. I also argue that the view defended in this paper does not imply - as some think - that the consent-receiver could wrong the consent-giver without being able to know that this is the case.